2019
DOI: 10.1038/s41559-019-0891-5
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of social relationships in the collective motion of bird flocks

Abstract: Supplementary Fig. 1 | Flock morphology and evidence of pairing for flocks #2 to #6. a1-a5, Spatial distributions and velocities of birds in three-dimensional space. Paired birds are colored in red. b1-b5, Radial distribution functions G(r). c1-c5, Joint PDFs of D i, n=1 and D i, n=2 . Supplementary Fig. 2 | Pairing causes variations in local interaction for flocks #2 to #6. a1-a5, Change of distance between a bird and its nearest neighbour at time 0. Flock #6 shows a somewhat different trend from the other fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 52 publications
9
88
0
2
Order By: Relevance
“…This may arise from physiological and behavioural differences linked to social attraction [62] and the number of neighbours an individual responds to [63], as well as from differences in body shape or manoeuvrability (especially for groups moving in water or air). Furthermore, individuals with stronger social affiliations tend to cluster within groups and occupy more posterior positions, such as jackdaws (Corvus monedula) flying in pair formation in mixed-species flocks [64,65]. Also, individual heterogeneity in sensory performance may affect spatial positioning, such as the cataract formation induced by certain parasites [66].…”
Section: Within-group Positioningmentioning
confidence: 99%
See 1 more Smart Citation
“…This may arise from physiological and behavioural differences linked to social attraction [62] and the number of neighbours an individual responds to [63], as well as from differences in body shape or manoeuvrability (especially for groups moving in water or air). Furthermore, individuals with stronger social affiliations tend to cluster within groups and occupy more posterior positions, such as jackdaws (Corvus monedula) flying in pair formation in mixed-species flocks [64,65]. Also, individual heterogeneity in sensory performance may affect spatial positioning, such as the cataract formation induced by certain parasites [66].…”
Section: Within-group Positioningmentioning
confidence: 99%
“…Phenotypes may also opt to remain solitary, such as those with high resource requirements to avoid competition with groupmates. As grouping with others can be more energetically efficient than staying alone [64,88], animals with low energy reserves or low aerobic scope may be more compelled to (stay in their) group to reduce energetic costs of movement. Importantly, the overall size of the group shifts the costs and benefits and thereby the relative trade-offs that motivate individual phenotypes to join the group.…”
Section: Fission-fusion Dynamics and Among-group Assortmentmentioning
confidence: 99%
“…figure S4), we find that birds prefer to fly side by side, in that the most probable location for a neighbouring bird was at dWing=1.0 m (2.8 jackdaw body lengths) and dMove=0. In a previous study [55], we found that these anisotropic spatial distributions of neighbours become isotropic for large topological distance (as in starlings [48]), a feature that we used to estimate the interaction range. We found that birds not part of a bonded pair typically interacted with 7 to 8 neighbours [55].…”
Section: Resultsmentioning
confidence: 77%
“…These interactions are treated as social "forces" [43] imposed by the presence of nearby neighbours that thus determine the acceleration of each agent. Although many empirical measurements of bird flocks have been made [44,45,[54][55][56][46][47][48][49][50][51][52][53], the fundamental interaction rules assumed in the models have still not been fully tested. In particular, the effective attractive and repulsive forces that birds experience while flying in large flocks has not been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation